Dinâmica fluvial e urbanização na bacia do Ribeirão Itapetinga município de Atibaia - SP: subsídios para o ensino de Geografia - Souza, Luís Gustavo Campos (Universidade Federal de São Carlos, 2016)
Understanding the social and environmental processes occurring in a watershed, and creating educational strategies to facilitate the mediation of knowledge related to the environment of contextualized way emerge as a priority in the contemporary world. Thus, the objectives of this study was the analysis of natural and human constraints active in fluvial dynamics of the basin of Ribeirão Itapetinga, Atibaia-SP and the development of geography teaching activities for students of the 8th year of a state school of São Paulo, in the context of Milieu Analysis, using the watershed as a spatial unit of analysis. The research was divided into two chapters. The first deals with the analysis of natural and human factors working in the area of the basin, such as average rainfall, geomorphology and types of use and occupation of land. The second chapter relates to the application of teaching-learning approaches for students of a public school, supported by the information in the study area. Among the conditions that influence the dynamics of river basin are: waterproofing and soil erosion, problems in the planning of urban drainage, irregular occupation of river plains, deforestation, lack of riparian vegetation at certain points. Among the natural order factors, the high average precipitation and relief features were the most decisive. The educational activities were very important to the expansion of knowledge of the students, as they facilitated the process of teaching and learning, making it more meaningful and oriented citizenship
Fluvial dynamics and urbanization in the basin of RIbeirão Itapetinga, Atibaia-SP: subsidies for geography teaching
Keywords: Bacias hidrográficas; Geografia - Estudo e ensino; Watersheds; Dinâmica fluvial; Fluvial Dynamics; Atividades de ensino; Teaching activities; OUTROS